Journalism at the Periphery - Tandoc Jr., Edson C. (2019)
The increasing influence of actors who might not fit into traditional definitions of a journalist but are taking part in processes that produce journalism has attracted scholarly attention. They have been called interlopers, strangers, new entrants, peripheral, and emergent actors, among others. As journalism scholars grapple with how to refer to these actors, it is important to reflect on the assumptions that underlie emerging labels. These include: 1) what journalistic tasks are involved; 2) how and why these journalistic tasks are performed; 3) who is making the definition; and 4) where and when these actors are located. However, journalism being the centre of our investigation should not automatically assume that it is at the centre of social life. So, it might also be that for the technological field, journalism is at the periphery; that for these technology-oriented actors whose influence across fields is increasing, journalists and what they do are at the periphery. For a field that supposedly plays an important role in public life, this has important implications.